Evaluation of the clinical sensitivity for the quantification of human immunodeficiency virus type 1 RNA in plasma: Comparison of the new COBAS TaqMan HIV-1 with three current HIV-RNA assays--LCx HIV RNA quantitative, VERSANT HIV-1 RNA 3.0 (bDNA) and COBA - Katsoulidou, A; Petrodaskalaki, M.; Sypsa, V; Papachristou, E.; Anastassopoulou, C. G.; Gargalianos, P; Karafoulidou, A.; Lazanas, M; Kordossis, T.; Andoniadou, A.; Hatzakis, A (J Virol MethodsJ Virol MethodsJ Virol Methods, 2006)
The COBAS TaqMan HIV-1 test (Roche Diagnostics) was compared with the LCx HIV RNA quantitative assay (Abbott Laboratories), the Versant HIV-1 RNA 3.0 (bDNA) assay (Bayer) and the COBAS Amplicor HIV-1 Monitor v1.5 test (Roche Diagnostics), using plasma samples of various viral load levels from HIV-1-infected individuals. In the comparison of TaqMan with LCx, TaqMan identified as positive 77.5% of the 240 samples versus 72.1% identified by LCx assay, while their overall agreement was 94.6% and the quantitative results of samples that were positive by both methods were strongly correlated (r=0.91). Similarly, in the comparison of TaqMan with bDNA 3.0, both methods identified 76.3% of the 177 samples as positive, while their overall agreement was 95.5% and the quantitative results of samples that were positive by both methods were strongly correlated (r=0.95). Finally, in the comparison of TaqMan with Monitor v1.5, TaqMan identified 79.5% of the 156 samples as positive versus 80.1% identified by Monitor v1.5, while their overall agreement was 95.5% and the quantitative results of samples that were positive by both methods were strongly correlated (r=0.96). In conclusion, the new COBAS TaqMan HIV-1 test showed excellent agreement with other widely used commercially available tests for the quantitation of HIV-1 viral load.
Keywords: *Viral Load; HIV Infections/*virology; HIV-1/isolation & purification/*physiology; Humans; Reagent Kits, Diagnostic; RNA, Viral/*blood; Sensitivity and Specificity; Statistics as Topic